Instructional Management of Islamic Education in Primary School - Husnani Husnani; Yasir Arafat; Happy Fitria (Universitas Bengkulu, 2020)
This study determined the instructional management of Islamic education in Primary School 25 Gelumbang. This study used qualitative method and the focus was instructional management. The instruments were observation, interview and documentation. The results showed that there were steps in instructional management such planning, implementing, organizing and monitoring. Then in supervision, the teacher made a breakthrough by involving parents and homeroom teachers in controlling their children to memorize short letters and asmaul husna given.